Screening of High Temperature Tolerant Tomato Genotypes for Their Fruit Mineral Content - Dere, Sultan; Daşgan, Hayriye Yıldız; Kafkas, Nesibe Ebru; Akhoundnejad, Yelderem (Yüzüncü Yıl Üniversitesi Tarım Bilimleri Dergisi, 2018)
Agriculture is at the forefront of the sectors that will be most affected by climate change. It is inevitable that Turkey is exposed to the negative effects of climate change due to its geographical location. The development of new high temperature tolerant varieties is seen as an important economic measure in the adaptation to climate change. In this study, heat temparature tolerant tomato genotypes were investigated for their fruit mineral content. For this purpose, twenty tolerant tomatoes from the gene pool of the Çukurova University, Department of Horticulture the and two commerical cultivars were grown in the open field conditions during 2016 spring and summer periods in Adana, Turkey. Tomato fruits grown under control and high temperature stresses conditions were analyzed for phosphorus, potassium, calcium, magnesium, iron, manganese, copper and zinc. According to heat stress effects on the tomato fruit mineral content, the macronutrients were ordered P, K, Ca, Mg from the least affected to the most affected. Moreover, the micro-nutrients were ordered Cu, Fe and Zn from the least affected to the most affected. In the present study heat tolerant tomato genotypes showed better performance and their mineral content most cases were higher than mineral content of the control trade cultivars.
Keywords: Calcium; Copper; İron; Magnesium; Phosphorus; Potassium; Solanum lycopersicum L.; Zinc